Prevalence of Mental Distress and Associated Factors among Samara University Students, Northeast Ethiopia - Tesfaye Kelemu, Robel (Depress Res Treat, 2020)
BACKGROUND: Empirical findings have indicated that higher institution students experience a higher prevalence of mental distress compared to the general population. Understanding the magnitude and associated factors of mental distress in university students would be helpful to practitioners and policymakers in Ethiopia. The aim of the present study was to examine the prevalence and associated factors of mental distress among Samara university students, Northeast Ethiopia. METHODS: Institution based cross-sectional study design was conducted in Samara university from December to June 2018. A simple random sampling technique was employed to select the study participants. Self-Reporting Questionnaire-20 (SRQ-20) was used to measure the mental distress of students. Multivariable logistic regression modeling was used to examine the association between sociodemographic and psychosocial factors with the mental distress of students. RESULTS: The proportion of students with mental distress were found to be 53.2% (95% confidence interval [CI]: 48.0%, 58.0%). Female students were more likely to be mentally distressed compared to male students (adjusted odds ratio [AOR]: 4.66; 95% CI: 2.81, 7.71). Ever khat use (AOR: 3.09; 95% CI: 1.74, 5.50) and poor sleep quality (AOR: 2.23; 95% CI: 1.12, 3.66) were significantly associated with mental distress of students. CONCLUSION: Our study indicates that the proportion of mental distress was found to be higher among Samara university students as compared to previously published studies in Ethiopia. Female students, ever khat users and those with poor sleep quality were associated with mental distress. There is a need for evidence-based interventional strategies such as self-help measures, sleep hygiene and peer support, as well as professional mental health services as part of student health services that would be helpful to reduce the burden of mental distress of students.